Uncertain private benefits and the decision to go public - Olaf Ehrhardt; Henry Lahr (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
This paper focuses on the decision to go public when both seller and potential buyers have private benefits of control. The basic model by Zingales (1995) is extended to account for uncertainty of private benefits. This leads to new implications for the sales process, ownership structure, measurement of private benefits and the efficiency of takeover regimes. The optimal way to sell the company differs from the model with perfect information in that the incumbent always choses to go public instead of selling directly to a potential rival whenever the rival is expected to increase cash flow but not necessarily total firm value. IPO price and volume are lower than under perfect information which induces a socially non-optimal solution in takeover transactions. Imperfect information also explains post-IPO underperformance of firms which are not subject to control transfers. To compensate shareholders for potential losses during the sales process, the offering price has to be lower than under perfect information. This provides the basis for a differential stock price performance depending on the buyer taking over or not. Furthermore, an overestimation bias exists in prior estimates of control premiums, because some firms going public are never sold but nevertheless provide private benefits. Finally, mandatory tender offers in the form of a fair price rule and an equal opportunity rule are discussed, which indicate that the social superiority of either rule is strongly dependent on the empirical distribution characteristics of private benefits.
Keywords: G14; G32; G34; 330; initial public offerings (IPOs); corporate control; private benefits; long-run performance; mandatory bid